ENVIRONMENTAL PROTECTION FROM THE PERSPECTIVES OF INDONESIAN, SUFI AND UNITED KINGDOM MUSLIM ENVIRONMENTALISTS - Bambang Irawan (Center for Research and Development of Religious Literature and Heritage, 2016)
The challenge posed by the world’s current environmental crisis has elicited a response from mainstream world religions in the form of efforts to construct an environmental ethics, based on religious and spiritual values. Suggestions for protecting and conserving the environment are a very ancient and fundamental aspect of religious teaching. The author will explore the perspectives of a number of environmental thinkers, including Fachruddin Mangunjaya of Indonesia, Hossein Nasr as a representative of Sufism, and Fazlun Khalid of the United Kingdom. The paper draws on structured and unstructured interviews with these thinkers and on exploration of their published works on nature conservation. From these sources the author has realized the urgency for religious communities to engage in sustaining the planet. The author has also identified the means to utilize and empower religious doctrines for environmental conservation. From these three sources we can learn strategies for elaborating productive Islamic values of environmental conservation and promoting a greater need of engagement and collaboration among them in initiating practical conservation projects.